Cannulation strategies for acute type A dissection—role of central cannulation. (31st March 2022) - Ramaprabhu, Krithika; Saran, Nishant; Dearani, Joseph; Lahr, Brian; Schaff, Hartzell; Greason, Kevin; Yalamuri, Suraj; Mangukia, Chirantan; Stulak, John; Bagameri, Gabor; Crestanello, Juan; Pochettino, Alberto
Abstract: OBJECTIVES: The purpose of this study was to assess the safety and efficacy of direct cannulation of the ascending aorta in comparison with cannulating peripheral arteries. METHODS: We retrospectively analysed type A dissection patients [ n = 107; median (interquartile range [IQR]) age, 64 [53–73] years] from January 2008 to March 2018. The cohort was divided into 2 groups: direct ascending aorta cannulation (group A, n = 47; median [IQR] age, 69 [54–74] years; 34% female) and non-aortic cannulation (group B, n = 60; median [IQR] age, 62 [52–72] years; 20% female). Postoperative outcomes and long-term survival were compared. RESULTS: Baseline characteristics were not significantly different between the 2 groups, except for higher creatinine in group B (median 0.9 vs 1.1, P = 0.028) and higher prevalence of dyslipidaemia in group A (58.7% vs 38.3%, P = 0.037). Overall early mortality was 12.1% ( n = 13); 12.8% ( n = 6) in group A and 11.7% ( n = 7) in group B ( P = 0.863). The incidence of stroke was 10.6% ( n = 5) in group A and 6.7% ( n = 4) in group B ( P = 0.463). After adjusting for CPB and circulatory arrest times, there was no group difference in the length of ICU ( P = 0.257) or hospital stay ( P = 0.118), all-cause reoperation ( P = 0.709), peak postoperative creatinine ( P = 0.426) and lactate values ( n = 60; P = 0.862). Overall survival at 1, 3 and 5 years was 84%, 78% and 73%, respectively, with no difference between the 2 groups after adjustment ( P = 0.629). CONCLUSIONS: Direct cannulation of the ascending aorta is a safe cannulation strategy for type A dissection repair, offering the opportunity for rapid arterial cannulation and antegrade perfusion. Abstract : Effective cardiopulmonary bypass (CPB) at the time of type A dissection repair is key to avoid malperfusion and ensure optimum outcomes [1, 2].